Effects of using the systemic approach on learning some fencing skills for junior fencers - Al-Bhery, A. R.; Salah El-Din, E. S.; Nabil Abd El-Aziz, S. I. (World Journal of Sport Sciences, 2010)
Fencing, as a sport, has undergone several technological advancements and developments. These developments, in turn, led to new modifications and changes in the international rules and regulations to increase the difficulty level of the game. Systemic approach is one of the modern approaches applied by educational researchers to understand phenomena with all its various and inter-connected aspects. The current research aimed at identifying the effects of using the systemic approach on cognitive acquisition and learning some fencing skills besides identifying the sample members' reflections on using the systemic approach. Sample (18 fencers) was randomly chosen from "The Military Institution" sports club and divided into two equivalent groups (9 fencers each). Results indicated statistically significant differences between the means of pre- and post- tests of the experimental group on the performance level and cognitive acquisition in favor of the posttest. The percentage of members who agreed on using the systemic approach is far greater than those who did not agree.